2017
DOI: 10.1186/s13075-017-1225-0
|View full text |Cite
|
Sign up to set email alerts
|

Osteoarthritis-associated basic calcium phosphate crystals activate membrane proximal kinases in human innate immune cells

Abstract: BackgroundOsteoarthritis (OA) is a chronic debilitating joint disorder of particularly high prevalence in the elderly population. Intra-articular basic calcium phosphate (BCP) crystals are present in the majority of OA joints and are associated with severe degeneration. They are known to activate macrophages, synovial fibroblasts, and articular chondrocytes, resulting in increased cell proliferation and the production of pro-inflammatory cytokines and matrix metalloproteases (MMPs). This suggests a pathogenic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
36
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 44 publications
(36 citation statements)
references
References 56 publications
0
36
0
Order By: Relevance
“…B). We have previously demonstrated that DAMPS, including BCP crystals and cholesterol crystals, drive S100A8 expression in a Syk/PI3K and Erk dependent manner, and while heme (50 μM) was found to induce MAP kinase phosphorylation within 5 min of incubation (Supplementary Material; Supplementary Fig. 1) in human Mϕ s, pretreatment with the Syk inhibitor, piceatannol, or the Erk inhibitor, PD98059, did not affect heme‐induced S100A8 gene expression, indicating that Syk signaling does not mediate the effects of heme on S100A8 expression.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…B). We have previously demonstrated that DAMPS, including BCP crystals and cholesterol crystals, drive S100A8 expression in a Syk/PI3K and Erk dependent manner, and while heme (50 μM) was found to induce MAP kinase phosphorylation within 5 min of incubation (Supplementary Material; Supplementary Fig. 1) in human Mϕ s, pretreatment with the Syk inhibitor, piceatannol, or the Erk inhibitor, PD98059, did not affect heme‐induced S100A8 gene expression, indicating that Syk signaling does not mediate the effects of heme on S100A8 expression.…”
Section: Resultsmentioning
confidence: 99%
“…High concentrations of S100A8 and S100A9 are reported in inflammatory conditions, such as rheumatoid arthritis, myocardial infarction, and Crohn's disease, and these proteins may exert some of their effects by enabling NLRP3 inflammasome formation and IL‐1β processing via TLR4‐ and reactive oxygen species‐dependent mechanisms . Furthermore, major DAMPs, such as basic calcium phosphate (BCP), associated with osteoarthritis, and cholesterol have been shown to induce S100 protein expression in immune cells …”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, humans with obesity have elevated blood LPS levels. LPS activates caspase-4/5/11, which initiates pyroptosis via the noncanonical inflammasome pathway [99] at both the systemic and tissue levels, leading to increased inflammatory chondrocyte death and loss of cartilage.…”
Section: Pyroptosis Is Related To Oa Risk Factorsmentioning
confidence: 99%
“…We recently demonstrated that, like MSU crystals, BCP crystals also activate, Syk, and its downstream interacting partner, PI3K, in primary macrophages, and that pharmacological inhibition of these kinases leads to reduced MMP expression and pro-inflammatory cytokine production ( 53 , 54 ). Whether Syk and/or PI3K activity is heightened in OA joints is yet to be determined, however, targeting membrane-proximal events induced by BCP crystals is a therapeutic option worth exploring.…”
Section: Calcium-containing Crystals In Oa and Cppd Diseasementioning
confidence: 99%